Full Solar-Spectrum Power-Generation System Based on High Efficiency and Wide Spectral Splitter Film and Fresnel Lens - Dong Wang; Houzhi Cai; Ou Yang (IEEE Access, 2021)
Based on high efficiency and wide spectral splitter film and Fresnel lens, we have theoretically investigated a full solar-spectrum power-generation system. Designed nano-multilayers are fabricated on Fresnel lens. Then short wavelengths (400 nm ~ 1100 nm) of solar-spectrum can be transmitted 95% to the solar cell, and long wavelengths (1100 nm ~ 2500 nm) of solar-spectrum can be reflected 90% and focused to the thermoelectric cell. This system can combine the efficiency of solar cells and thermoelectric cells to generate electricity across the entire solar spectrum. In theory, the limit for total conversion efficiency is $η =56.64$ %.